Correlation between Knowledge and Attitude with Compliance with Blood Supplement Tablet Consumption in SMAN 10 Students in the Working Area of Puskesmas Andalas, Padang City - Hadi, Al; Novrita, Sisri (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2023)
The high incidence of anemia occurs in the adolescent age group and female sex. In preventing anemia and reducing the incidence of anemia in Indonesia, the government is holding a blood-added tablet supplementation program for young girls at school. To support the program, this research was carried out with the aim of knowing the relationship between knowledge and attitude with adherence to blood supplement consumption by female students of SMAN 10 in the working area of the Andalas Health Center, Padang City. This research was conducted from March to June 2023. The method used was an observational analytic design, the sampling technique used was purposive sampling which met the inclusion and exclusion criteria. The sample used in this study was female students of SMAN 10 in the working area of the Andalas Public Health Center, Padang City. The results of the univariate test of SMAN 10 female students in the work area of the Andalas Health Center, Padang City, most of them had high knowledge (66.5%), negative attitudes (55.7%), low compliance (74.3%). Then the results of the chi square test obtained that the relationship between knowledge and attitudes did not have a significant relationship with a P value of 0.542 (≥ 0.05), and the relationship between attitude and adherence to consumption of iron tablets had a significant relationship with a P value (≤ 0.05).